HUBUNGAN MASALAH MENYUSUI DENGAN PEMBERIAN ASI - Raja Resta Asnawati; Widia Lestari; Oswati Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Purpose: This study aims to determine the relationship between approach breastfeeding problems and breastfeeding method. Methods: The design in this study used a descriptive correlation withapproach cross sectional approach breastfeeding, with a total sample of 60 breastfeeding mothers who were taken based on inclusion criteria using accidental sampling techniques. The analysis used was univariate and bivariate analysis, using the chi-square test. Results: The majority of breastfeeding was exclusive breastfeeding 32 respondents (53.3%), the majority of breastfeeding problems that were most often found in the first week were flat / immersed nipples as many as 31 respondents (51.7%), swollen breasts by 30 respondents (50%), Breast milk does not come out / a little as many as 36 respondents (60%), except for blisters / sore nipples, red breasts and pain, the majority occurred at week 2-1 months as many as 18 respondents (30%) and 20 respondents (33.3 %). The results of statistical tests showed that there was a significant relationship between breastfeeding problems and breastfeeding, it was found that the nipples were flat / immersed p value (0.001)<(0.05), swollen breasts p value (0.029)<(0.05), nipple blisters / wounds. p value (0.018)<(0.05), red breast and pain p value (0.010)<(0.05), breast milk did not come out / little p value (0.029)<(0.05). Conclusion: Breastfeeding problems experienced by mothers are related to the success of mothers in giving exclusive breastfeeding. Suggestion: Health workers, it is hoped should prevent and overcome early breastfeeding problems experienced by mothers so that mothers can successfully provide exclusive breastfeeding.Keywords: breastfeeding problem; breastfeeding.